2018
DOI: 10.1097/md.0000000000012489
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between short telomere length and stroke

Abstract: Background:Several epidemiological studies had been carried out in different population cohorts to estimate the relationship between the shortened telomere length and stroke. However, the results still remained dispute. Consequently, we conducted this meta-analysis to estimate the relationship between them.Methods:PubMed, EMBASE, and Web of Science were systematically searched for related articles to evaluate the association between “stroke” and “telomere length. STATA 12.0 software was used to perform the met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 47 publications
2
19
0
Order By: Relevance
“…Similar results were also found in a pool-analysis [35]. In contrast to a meta-analysis that aggregated data from 11 cohort studies, the association between TL and stroke was found to be significant in a pooled analysis, but was not found in subgroup analysis, in either the prospective or retrospective study subgroups [36].…”
Section: Discussionsupporting
confidence: 70%
“…Similar results were also found in a pool-analysis [35]. In contrast to a meta-analysis that aggregated data from 11 cohort studies, the association between TL and stroke was found to be significant in a pooled analysis, but was not found in subgroup analysis, in either the prospective or retrospective study subgroups [36].…”
Section: Discussionsupporting
confidence: 70%
“…Despite previous retrospective observational studies reporting an TL-stroke association, such a relationship has not been firmly supported by evidence from prospective cohort studies. Subgroup analysis of four meta-analysis (stratified by study design) have shown consistent results that shorter TL were not significantly associated with stroke risk in prospective studies or in studies with a high quality score [ 18 , 19 , 33 , 34 ]. In a recent meta-analysis, shorter TL was associated with a significant 11% higher risk for stroke (RR = 1.12, 95% CI 1.05–1.19), although with significant heterogeneity between studies ( I 2 = 81.1%, P het < 0.001) [ 33 ].…”
Section: Discussionmentioning
confidence: 88%
“…In contrast, evidence also suggests that shorter telomeres were not significantly associated with stroke risk [ 15 17 ]. However, meta-analysis have shown that there were less certain results to support the relationship between TL and stroke [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, telomere length has been most extensively researched and was found to be shorter in various somatic conditions 8 , all-cause mortality 9,10 and a range of psychiatric disorders 11 . Advanced epigenetic age has also been linked to worse somatic health, mortality 12 , depressive disorder 7,13 and post-traumatic stress disorder 14 , although some studies have found associations with the opposite direction of effect 15,16 .…”
Section: Introductionmentioning
confidence: 99%